Effects of stone terraces on crop yields and farm profitability: Results of on-farm research in Tigray, northern Ethiopia - Gebremedhin, Berhanu; Swinton, S.M.; Tilahun, Y. (1999)
This study was conducted in Tigray, northern Ethiopia to determine the yield and farm profitability impact of stone terraces. Seventy terraced and 70 non-conserved plots were equally divided between wheat (Triticum aestivum) and faba beans (Vicia faba). Two quadrates each 8 m (86 ft2) were marked on each terraced plot: one just above the terrace (soil accumulation zone) and another one parallel to this but below the next upper terrace (soil loss zone). Only one quadrate (control zone) was marked on each of the non-conserved plots. Results indicate that (1) grain and straw yields for both crops were significantly higher in the soil accumulation zone than in the soil loss zone or in the non-terraced control plots; (2) grain and straw yields from the soil accumulation zone were more stable than those from control zone; (3) over a 30-yr planning horizone, stone terrace yielded a 50% rate of return, roughly equivalent to reported farmer discount in Ethiopia.